2014
DOI: 10.25103/jestr.073.29
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Stone Waste in the Development of Value Added Products: A State of the Art Review

Abstract: The utilisation of stone waste, in the form of mineral admixture as a pozzolanic and non-pozzolanic material for mortar and concrete has received considerable attention in recent years. This interest is part of the widely spread attention directed towards the utilisation of wastes and industrial by-products in order to minimise Portland cement (PC) and sand consumption, the utilisationof which being environmentally damaging. Another reason is that mortar and concrete, which contain pozzolanic as well as non-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Slurry affects the productivity of the land as a result of decreasing porosity, and water absorption and also percolation. Additionally, due to long-term deposition, slurry dumping areas are not able to support vegetation and remain degraded, while the finer particles seriously influence underground water availability and stop the flow regime of aquifers [5]. In addition, cement is the most environment-pollutant component of concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slurry affects the productivity of the land as a result of decreasing porosity, and water absorption and also percolation. Additionally, due to long-term deposition, slurry dumping areas are not able to support vegetation and remain degraded, while the finer particles seriously influence underground water availability and stop the flow regime of aquifers [5]. In addition, cement is the most environment-pollutant component of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researches have shown that the incorporation of several types of stone waste in concrete production results in lower slump of fresh concrete in comparison with traditional concrete, and increasing the waste content further lowers the slump. It is argued that the particle size of the stone aggregates is the reason behind this lower slump [5].…”
Section: Introductionmentioning
confidence: 99%
“…The stone powder is mainly composed of silicon dioxide, calcium carbonate, and other aluminum silicate containing calcium [17], which is identified by XRD measurement shown in the lower red curve in Figure 1 and EDS element detection presented in Table S1 in the supplementary materials. The stone powder was mixed with concrete and sand, and then fabricated into aerated bricks.…”
Section: Resultsmentioning
confidence: 99%
“…The solidification, also known under the term stabilization, is based on the physical encapsulation of the contaminants and their chemical fixation in the solid matrix of a newly generated product. The input material and waste are intensively mixed in continuous or batch wise operated mixers with additives like cement, limestone, gypsum, fly ash or blast furnace slag and water [Lakhani et al 2014]. In the case of the physical encapsulation, the input material is merged by the binders and additives.…”
Section: Solidificationmentioning
confidence: 99%